A research environment for teacher-driven research – some demands and possibilities. Issue 1 (20th September 2019) - Andrée, Maria; Eriksson, Inger
Abstract : Purpose: The purpose of this paper is to reflect upon demands of and possibilities for establishing a space for conducting and supporting high-quality research in schools. In the article the authors reflect upon experiences in establishing a research environment for teachers called Stockholm Teaching & Learning Studies (STLS). The article focusses some of the tensions that have been emerging in attempting to build an infrastructure for teacher-driven research and discusses the transformative potential of those tensions. Design/methodology/approach: The article draws on the authors' experiences in establishing STLS as a research environment for teachers by drawing on a framework of cultural-historical activity theory. The article applies the notions of contradictions and tensions as driving forces for development of activity. Findings: The specific tensions that have been negotiated in the establishment of STLS are tensions between developing public knowledge vs local knowledge, tensions in knowledge cultures between oral and text-based ways of sharing knowledge, tensions in research interests and tensions in ownership. These tensions relate to knowledge production as embedded in institutional life and constrained by institutional boundaries in contemporary society. Originality/value: Today, there is a growing amount of collaborative research that connects elementary and secondary teachers in research projects with university-based researchers. However, this does not guarantee projects that will address everyday problems of teachers or that teachers will be acknowledged as researchers in the end.